Glu298Asp polymorphism of the endothelial nitric oxide synthase gene and plasma concentrations of asymmetric dimethylarginine in Turkish pre-eclamptic women without fetal growth retardation - Turan, Fahri; Ilhan, Necip; Kaman, Dilara; Ates, Kadir; Kafkasli, Ayse (Wiley, 2010)
Aims: Pre-eclampsia (PE) is a leading cause of maternal death worldwide, affecting 3 to 5% of all pregnancies. We analyzed the Glu298Asp polymorphism of the endothelial nitric oxide synthase gene and asymmetric dimethylarginine (ADMA) in 55 Turkish patients with PE without fetal growth retardation (FGR) and in 54 healthy pregnant women. Methods: Restriction fragment length polymorphism analysis of Glu298Asp of the endothelial nitric oxide synthase gene was evaluated by amplification of genomic DNA isolated from whole blood followed by digestion with the restriction enzyme Frio. PE was defined according to the Working Group2000 criteria as high blood pressure (>= 140/90 mmHg after 20 weeks of gestation) and proteinuria (> 300 mg/24 h). We excluded the women with FGR Serum arginine, with only ADMA and symmetric dimethylarginine (SDMA) levels measured by high-performance liquid chromatography. Results: Genotypes were defined as GG, GT and TT according to the presence of the G and T alleles. In this case-control study, we did not find any significant difference in either the genotypic distribution or allelic frequency of Glu298Asp gene polymorphism between the pre-eclamptic patients and healthy pregnant women. Serum ADMA, arginine and SDMA levels were higher in patients with PE compared with healthy pregnant women (respectively, P < 0.0001, P < 0.0001, P < 0.0001). Conclusions: The results suggested a lack of association between the Glu298Asp gene polymorphism and pre-eclampsia without FGR in the Turkish population. But elevated ADMA and SDMA levels suggest that ADMA has a role in the pathogenesis of PE.
Keywords: ADMA; eNOS gene polymorphism; pre-eclampsia